The role of instagram in building brand awareness - Christian Aditya Perdana; Dindin Dimyati (Enrichment : Journal of Management, 2023)
This study aims to determine the role of Instagram social media in building @iDeviceStoreJogja brand awareness and to find out the advantages and disadvantages of Instagram social media in building @iDeviceStoreJogja brand awareness. This type of research is survey research using a quantitative approach. The subjects in this study were followers of the @iDeviceStoreJogja account. The function of Instagram in building brand awareness is the subject of this research. Researchers also use secondary data to support research results taken from pre-existing sources of information, namely data via websites and YouTube channels. The data analysis technique used is quantitative analysis, where the data obtained is expressed in numbers. Then the calculation or processing is done statistically with the help of the Statistical Package for Social Science or SPSS program. The test results obtained show that the use of Instagram on the @iDeviceStoreJogja account is significantly and positively effective in building brand awareness. This is evidenced by the value????ℎ????????????????????obtained is 32.241 and a significance of 0.000, which means that the significance value is < α = 0.05. From the test results obtained, it shows that the use of Instagram on the @iDeviceStoreJogja account is significantly and positively effective in building brand awareness.